Estimation of the relative throughput of requesting airspace surveillance systems - Tkach, M.G.; Svyd, I.V.; Vorgul, O.V.; Starokozhev, S.V.; Maltsev, O.S.; Hlushchenko, A.O. (Radiotekhnika, 2022)
The paper considers a method for increasing the relative throughput of requesting airspace surveillance radar systems, in which it is proposed to use broadband signals as request and response signals. Thanks to the use of broadband signals, it is possible to reduce significantly the detection range of such response signals with the required quality indicators by means of radio reconnaissance, which practically excludes the possibility for the interested party to use the response signals of an aircraft responder both for long-range detection of air objects and for measuring their coordinates. And, as a result, it makes it possible to exclude unauthorized use of an aircraft responder of requesting radar systems for airspace monitoring by an interested party to suppress the response channel, and, consequently, increase the relative throughput of the considered information systems.